IMPLEMENTATION OF THE NEXT GENERATION SOCIAL WELFARE INFORMATION SYSTEM (SIKS-NG) IN SEMAMBUNG VILLAGE, WONOAYU DISTRICT, SIDOARJO REGENCY - YuliaSari, Della Putri; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze how the Next Generation Social Welfare Information System (SIKS-NG) is implemented in Semambung Village, Wonoayu District. This research applies the Edward III policy implementation model which includes four aspects, namely communication, resources, disposition, and bureaucratic structure. Methods: The research method used is qualitative descriptive, by collecting data through direct observation, in-depth interviews with village officials and SIKS-NG operators, as well as relevant supporting documentation. Data analysis was carried out using the Miles and Huberman interactive model which consisted of four stages, namely data collection, data reduction, data presentation, and conclusion drawn. Results: The results of the study showed that internal communication between the operator and the Head of the Welfare Section had gone quite well, but external communication with the community was still limited due to the absence of formal socialization. In terms of resources, facilities such as computers and printers are adequate, but unstable internet connections, lack of dedicated budgets, and reliance on a single operator hinder optimal application performance. Despite not obtaining special incentives, operators show high commitment and responsibility, reflecting a positive executor disposition. In terms of bureaucratic structure, the village government does not yet have a written Standard Operating Procedure (SOP) specifically for SIKS-NG, so the technical implementation still relies on verbal direction and work experience. Novelty: This study highlights the implementation of SIKS-NG in Semambung Village using an analysis of Edward III indicators. It reveals the absence of specific standard operating procedures (SOPs), limited public access to information, and limited resources, including a single operator and unstable internet connections. These findings serve as an important assessment for the development of social welfare e-government policies and the challenges of digital services in the village.